Processes and effects of correction with eyeglasses in a child with severe motor and intellectual disabilities: A case report. Issue 8 (2015) - Hirano, Daisuke; Minagawa, Chihiro; Umehara, Sachiko; Hayashi, Kaori; Onose, Yuka; Sekimori, Hidenobu; Taniguchi, Takamichi; Komachi, Yuko; Shimoizumi, Hideo; Niida, Takahiro
No abstract available